Strategi Guru Pendidikan Agama Islam Dalam Pembentukan Karakter Siswa di SD N 15 Ampang Gadang - Jelita Oktafiani; Puti Andam Dewi; Meli Sartika (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to describe the strategies of Islamic religious SD N 15 Ampang Gadang education teachers in building the character of student in schools, the condition of the character of student in schools, and the obstacles Islamic religious education teachers have in forming the character of student in schools. This research is a qualitative research with purposive sampling, namely the deputy head of the curriculum, teachers of Islamic religious education, and students of grades IV. This research shows that the strategy of Islamic religious education teachers in forming the character of students in schools is carried out by providing teaching and advice to children about the importance of character education, accustoming students to doing good activities or actions, and setting an example to students. The character of student at school is that students are not late for school, do assignments on time, participate in extracurricular activities, and return books that have been lent. The obstacles faced are school regulations that are not strict enough for students, as well as a lack of guidance and attention from parents. Based on these conditions, the teacher's efforts at school are to make rules in the classroom during the learning process and provide advice to students during and outside of class hours